Mechanically programmed 2D and 3D liquid crystal elastomers at macro- and microscale via two-step photocrosslinking. Issue 11 (14th February 2020) - Lee, Jieun; Guo, Yuanhang; Choi, Yu-Jin; Jung, Soonho; Seol, Daehee; Choi, Subi; Kim, Jae-Hyuk; Kim, Yunseok; Jeong, Kwang-Un; Ahn, Suk-kyun
Abstract : A facile method for fabricating 3D-shaped liquid crystal elastomers at the macro- and microscales was developed by mechanical programming coupled with two-step photocrosslinking. Abstract : Liquid crystal elastomers (LCEs) are a unique class of active materials with the largest known reversible shape transformation in the solid state. The shape change of LCEs is directed by programming their molecular orientation, and therefore, several strategies to control LC alignment have been developed. Although mechanical alignment coupled with a two-step crosslinking is commonly adopted for uniaxially-aligned monodomain LCE synthesis, the fabrication of 3D-shaped LCEs at the macro- and microscale has been rarely accomplished. Here, we report a facile processing method for fabricating 2D and 3D-shaped LCEs at the macro- and microscales at room temperature by mechanically programming ( i.e., stretching, pressing, embossing and UV-imprinting) the polydomain LCE, and subsequent photocrosslinking. The programmed LCEs exhibited a reversible shape change when exposed to thermal and chemical stimuli. Besides the programmed shape changes, the actuation strain can also be preprogrammed by adjusting the extent of elongation of a polydomain LCE. Furthermore, the LCE micropillar arrays prepared by UV-imprinting displayed a substantial change in pillar height in a reversible manner during thermal actuation. Our convenient method for fabricating reversible 2D and 3D-shaped LCEs from commercially available materials may expedite the potential applications of LCEs in actuators, soft robots, smart coatings, tunable optics and medicine.